2016
DOI: 10.1038/srep23029
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the IL27 gene in a Chinese Han population complicated with pre-eclampsia

Abstract: IL-27 could inhibit the development of Th17 cells, and the Th17/regulatory T-cell imbalance may reverse maternal tolerance in pre-eclampsia (PE). The aim of this study was to investigate the association between genetic polymorphisms in IL27 with PE. Three SNPs in IL27 (rs153109, rs17855750, and rs181206) were genotyped in a Chinese Han cohort of 1040 PE patients and 1247 normal pregnant women using the TaqMan allelic discrimination real-time PCR method. The CC genotypic distribution of rs153109 was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Studies of the Chinese Han population have reported that the vitamin D receptor gene with the G allele of rs2228570, the IL-10-1082A/G and -819T/C, IL-27 rs153109 and rs17855750 variants, as well as 11β-hydroxysteroid dehydrogenase and killer-cell immunoglobulin-like receptor genetic variations are related to PE (24-26). Cyclooxygenase-1195A homozygosity and variant growth arrest-specific 6 +1332 T allele were also indicated to correlate with a reduced PE risk in the Chinese Han population (27)(28)(29).…”
Section: Susceptibility Genesmentioning
confidence: 99%
“…Studies of the Chinese Han population have reported that the vitamin D receptor gene with the G allele of rs2228570, the IL-10-1082A/G and -819T/C, IL-27 rs153109 and rs17855750 variants, as well as 11β-hydroxysteroid dehydrogenase and killer-cell immunoglobulin-like receptor genetic variations are related to PE (24-26). Cyclooxygenase-1195A homozygosity and variant growth arrest-specific 6 +1332 T allele were also indicated to correlate with a reduced PE risk in the Chinese Han population (27)(28)(29).…”
Section: Susceptibility Genesmentioning
confidence: 99%
“…Results from studies regarding polymorphisms of IL‐27 gene are controversial. Liu et al reported that the CC genotype of rs153109 was associated with a higher risk of PE (OR = 1.54, 95% CI: [1.23‐1.93]), while the CT genotype was shown to be protective (OR = 0.74, 95% CI: [0.63‐0.88]). Distributions of genotypes and alleles of rs17855750 and rs181206 showed no difference in study cases and controls.…”
Section: Resultsmentioning
confidence: 99%
“…He and colleagues found a strong correlation between the IL-27- A964G variant and GD, but no correlation was found between autoimmune thyroid diseases and the IL-27- T4730C variant [ 84 ]. We obtained preliminary results in a pilot study in which we analyzed the possible role of the IL-27- T4730C polymorphism in Multiple Sclerosis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%